BUDIDAYA BENIH IKAN NILA (Oreochromis niloticus) PADA MEDIA RECIRCULATING AQUACULTURE SYSTEM (RAS) DAN SISTEM AERASI: BUDIDAYA BENIH IKAN NILA (Oreochromis niloticus) PADA MEDIA RECIRCULATING AQUACULTURE SYSTEM (RAS) DAN SISTEM AERASI - Asri, Yuliana; Septiana Dwiyanti; Laily Fitriani Mulyani (Journal of Fish Nutrition, 2025)
Tilapia, as a high-value consumption fish, is one of the main reasons why fish farmers choose it as a key aquaculture commodity whose cultivation technology continues to be developed. Flow-through water system is one of the commonly used methods in tilapia farming in Indonesia. However, this method has several drawbacks, such as the continuous use of large volumes of water. Additionally, the environmental impact is a concern, as uneaten feed and feces discharged through the pond's outlet can pose a threat to the surrounding environment. To address these issues, technological advancements in tilapia farming continue to be developed, including the implementation of Recirculating Aquaculture System (RAS) and aeration systems. The use of these two technologies aims to improve water quality, reduce excessive water usage, and minimize environmental impacts associated with tilapia aquaculture activities. This study compares the two systems—RAS and aeration—using tilapia fingerlings measuring 5–6 cm over a 20-day cultivation period. Water quality and growth data were analyzed descriptively. The results showed that ammonia levels in the RAS system reached 0.08 mg/L, which falls within the optimal range for tilapia cultivation. In contrast, the aeration system showed ammonia levels of 1.6 mg/L, which exceeds the optimal threshold. Based on these findings, it can be concluded that tilapia fingerling cultivation using the RAS system is more effective at stabilizing and reducing ammonia levels in the culture medium compared to the aeration system.